PENGUJIAN STRUKTUR MODAL OPTIMAL MELALUI POLA HUBUNGAN ANTAR VARIABEL LEVERAGE, PROFITABILITAS, DAN NILAI PERUSAHAAN - Harmono Harmono (Jurnal Keuangan dan Perbankan, 2010)
These research reviewed theoretical and empirical literature compared among thecapital structure theory, Modigliani and Miller model, traditional model, and combined withROE framework by Evans (2000) for testing optimum capital structure related with firmsvalue concepts. The research design of this study used descriptive and co-relational modelwith population which were some industries which had been published in Indonesia StockExchange, and purposive sampling for fulfillment of the capital structure assume, and rela-tionship with leverage concept. The finding of this research based on the descriptive and co-relational analysis was that, first, the average of capital structure for industries at level 55%consisted of; food and beverage 51%, automotive 51%, textile 68%, property 44%, andselected by descriptive analysis, the optimum capital structure analysis, in which debts tototal assets indicated at level 40%. The second, results of multiple regressions indicated thatfinancial performance had any significant to firm values, but not significant to financialleverage, and then the effect of leverage variable to firm value was significant. Thus, thetheoretical framework of optimum capital structure was testable having any correlation andsignificant with firms value.